Intravitreal Triamcinolone Acetonide in Treatment of Macular Edema Associated with Branch Retinal Venous Occlusion - U. P. Sinha, Deepak Mishra, Priyanka, Shekhar Chaudhry (International Journal of Innovative Research in Medical Science, 2017)
Purpose: - To study safety and efficacy of Intravitreal Triamcinolone accetonide as treatment of macular edema in cases of Branch retinal venous occlusion. Material & Method: - In a prospective study, 14 patients with BRVO with persistent macular edema were treated with intravitreal triamcinolone (4 mg) for macular edema. Snellen s visual acuity, intraocular Pressure (IOP), measurement of central macular thickness by OCT and frequency of complications were studied during follow up at 1 month and 3 month. Results: - In the present study, the median age of 14 patients was 48.5 yrs and median duration of symptoms before injection was 3 months. Mean baseline visual acuity was 0.10 ± 0.04 in affected eye. Mean visual acuity at 1 month follow up was 0.55± 0.17 and at 6 months was 0.48± 5.11 (n=8) in the affected eye. All patients except completed the 1 month examination while only 8 patient followed up to 3 months. The eyes with BRVO demonstrated a significant improvement in mean foveal thickness (Central macular thickness) Mean baseline foveal thickness as measured by OCT was 371 ±80.75 (n=14). At one month follow up, the mean foveal thickness was 227.2 + 44.4, and at three months the thickness was 243.75 ±29.46 (n=8). Two patients developed recurrences of macular edema, hence second injection of triamcinolone was given. Two patients developed early Posterior sub capsular cataract but surgery was not needed during the study period. One patient developed raised IOP for which was controlled by aqueous suppressants. Six patients lost follow-up at 3 months. No patients developed serious complication like Retinal detatchment, or endophthalmitis. Conclusion: - Intravitreal injection of triamcinolone accetonide may be effective in treatment of patients with persistant macular edema in BRVO. However, the significant effect may persis for one month and retreatment may be necessary in few patients. In this study, severe complications were not noted.